Mitigating Cyberattack Impacts on LFC-AVR Systems with High Renewable Penetration through Redundancy and Adaptive Kalman Filter - Pradana, Adlan; Nadarajah, Mithulananthan; Feng, Jiajie; Haque, Md. Mejbaul (Global Power, Energy and Communication Conference (Online), 2025)
The power system is a critical infrastructure underpinning modern civilization. Its importance has become even more pronounced in the context of global uncertainties, such as the Ukraine-Russia conflict and ongoing tensions in the Middle East, where power systems are frequently targeted in cyber warfare. In such scenarios, ensuring the resilience of Load Frequency Control (LFC) and Automatic Voltage Regulation (AVR) systems is paramount, especially in grids with high renewable energy penetration, where inherent uncertainties add further challenges. This paper proposes a robust mitigation strategy to address cyberattacks on multiarea LFC-AVR systems, including False Data Injection Attacks (FDIA), Denial of Service (DoS), and Replay Attacks. A redundancy-based communication framework is developed, leveraging three independent communication lines to ensure continuity of data integrity. When all redundant communication lines are compromised, an Adaptive Kalman Filter (AKF) is employed as a fallback mechanism. The AKF dynamically adjusts to cyberattack-induced anomalies and the inherent variability of renewable energy sources, enabling reliable state estimation and system recovery. The proposed system is tested under varying attack scenarios and renewable penetration levels. Results demonstrate that the combined redundancy and adaptive filtering approach effectively mitigate attack impacts while maintaining system stability, even in highly uncertain conditions. This research highlights the critical role of redundancy and adaptive control in safeguarding the resilience of modern power systems amidst escalating threats and uncertainties.